NIACIN AND NIACIN / LAROPIPRANT COMBINATION: OPENING NEW HOPES FOR DYSLIPIDEMIA AND CARDIOVASCULAR DISEASES WITH FEW NOVEL ACTIONS - KAORE S.N.; YADAV V.K.; KAORE N.M. (International Journal of Pharma and Bio Sciences, 2013)
Niacin (nicotinic acid- NA), B – complex vitamin, one of the oldest lipid modulating drugs used almost over 50 years, is the most effective option for raising HDL-C, lowering LDL-C and TG that carries the risk for cardiovacsular diseases like MI, but is largely underutilized due to flushing and hepatotoxicity discouraging its use in patients. Alternative strategies for regular niacin available are extended release niacin (ERN) with or without Laropiprant (DP1 antagonist, a prostanoid receptor) that decrease flushing, less/no hepatotoxicity, decrease BP, safe in diabetics and increase in patient compliance. Additional insights for niacin induced flushing and role in atherosclerosis, hypolipidemic actions revealed are discussed in detail. Novel actions of niacin in immune system improves peripheral mononuclear cells cell viability, decrease in genotoxic stress, drug for hyperphosphatemia, improvement in symptoms of Parkinsonism and psoriasis. If FDA clears the legal issues on the combination strategy of ERN with Laropiprant, it may further succeed in doing a comeback after a long time and will enable to fully exploit the therapeutic potential of niacin. The pharmacodynamics of Laropiprant and the combination of ERN and Laropiprant in reducing overall risk of cardiovascular diseases is discussed in detail.